ISOLASI DAN IDENTIFIKASI KOMPONEN KIMIA EKSTRAK N-HEKSAN KLIKA JAMBLANG (SYZYGIUM CUMINI L.) - Iramayasari Iramayasari (As-Syifaa Jurnal Farmasi, 2011)
Isolation and identification chemical component of n-Heksan ekstract Klika Jamblang (Syzygium cumini L.).Have been isolated and identification chemical component of n-Hexan extract of Klika Jamblang (Syzygium cumini L.).Extraction by refluks with using methanol, and partitioned with n-Hexan.   n-Hexan extract isolated by suction column method with using silica gel as adsorban and Hexan :Ethyl acetat (20:1, 20:1, 15:1, 10:1, 5:1, 1:1, 1:5, again with Ethyl acetate 50 ml and with methanol 50 ml), as elution liquid, obtained 9 fraction.Fraction Vb1 then purified with preparative TLC until obtained 1 purity compound.Fraction Vb1 analyzed by ultraviolet-visible spectroscophy wich shown absorbance in maximum 239 nm, where as infrared spectroscophy shown presence of –OH gropu, CH alipatyc group, alkyn group, RCN aromatic group, lakton group, cincin aromatic group, CH aromatic group and klorida aliphatic group. And analyzed by chemistry reaction, namely Liebermann-Buchard, Acid preklorate, Vanilin-Sulfat Acid, which show presence of steroid compound group. Keyword : Klika Jamblang (Syzygium cumini L.), Isolation  and identification,  KLT, steroid